Lactation opposes pappalysin‐1‐driven pregnancy‐associated breast cancer. Issue 4 (8th March 2016) - Takabatake, Yukie; Oxvig, Claus; Nagi, Chandandeep; Adelson, Kerin; Jaffer, Shabnam; Schmidt, Hank; Keely, Patricia J; Eliceiri, Kevin W; Mandeli, John; Germain, Doris
Abstract: Pregnancy is associated with a transient increase in risk for breast cancer. However, the mechanism underlying pregnancy‐associated breast cancer (PABC) is poorly understood. Here, we identify the protease pappalysin‐1 (PAPP‐A) as a pregnancy‐dependent oncogene. Transgenic expression of PAPP‐A in the mouse mammary gland during pregnancy and involution promotes the deposition of collagen. We demonstrate that collagen facilitates the proteolysis of IGFBP‐4 and IGFBP‐5 by PAPP‐A, resulting in increased proliferative signaling during gestation and a delayed involution. However, while studying the effect of lactation, we found that although PAPP‐A transgenic mice lactating for an extended period of time do not develop mammary tumors, those that lactate for a short period develop mammary tumors characterized by a tumor‐associated collagen signature (TACS‐3). Mechanistically, we found that the protective effect of lactation is associated with the expression of inhibitors of PAPP‐A, STC1, and STC2. Collectively, these results identify PAPP‐A as a pregnancy‐dependent oncogene while also showing that extended lactation is protective against PAPP‐A‐mediated carcinogenesis. Our results offer the first mechanism that explains the link between breast cancer, pregnancy, and breastfeeding. Synopsis: Pregnancy is associated with a transient risk of breast cancer. Here, the protease pappalysin‐1 (PAPP‐A) is identified as a possible pregnancy‐dependent oncogene whose function is limited during lactation. Transgenic expression of the protease pappalysin‐1 (PAPP‐A) in mouse mammary gland shows that it is a pregnancy‐associated oncogene. PAPP‐A proteolytic activity is activated by the increased deposition of collagen during pregnancy and involution. The oncogenic function of PAPP‐A is limited by lactation due to the expression of inhibitors of PAPP‐A during this phase. Abstract : Pregnancy is associated with a transient risk of breast cancer. Here, the protease pappalysin‐1 (PAPP‐A) is identified as a possible pregnancy‐dependent oncogene whose function is limited during lactation.